"Special Report: Infant Mortality in Memphis, ": by Aimee Edmondson, The Commercial Appeal, March 6, 2005, p. 1. Issue 4 (2nd October 2022) - Stuckey, Alex
: Alex Stuckey is an investigative reporter for the Houston Chronicle. She won a Pulitzer Prize in 2017 for a Salt Lake Tribune exposé on the cruel treatment of sexual assault survivors at Brigham Young University. Earlier this year, Stuckey accepted a Livingston Award—for journalists under thirty-five—for a series on families trapped in the state's underfunded mental health system. She was also named the 2022 star reporter of the year by Texas Managing Editors. Stuckey previously wrote for the Columbus Dispatch, Arizona Republic, and St. Louis Post-Dispatch.